Charge pumping measurements on differently passivated lateral 4H-SiC MOSFETs - Salinaro, Alberto; Pobegen, Gregor; Aichinger, Thomas; Zippelius, Bernd; Peters, Dethard P.; Friedrichs, Peter; Frey, Lothar (IEEE Transactions on Electron Devices, 2015)
This paper shows a successful transfer of the charge pumping (CP) method, which is extensively applied on silicon (Si) transistors, to Si carbide (SiC) lateral MOSFETs to characterize the quality of the SiC/SiO interface near the conduction and valence band edges. In particular, the constant base technique provides more accuracy and flexibility with respect to the most commonly used constant amplitude technique. Anomalous phenomena previously reported in literature, such as the so-called geometric component, are absent if the measurements are performed on transistors with optimized geometry and if the parameters of the applied CP gate pulses are carefully chosen. Furthermore, interface properties of gate oxides subjected to different postoxidation treatments are compared using this technique and the influence of the measurement parameters and temperature on the resulting CP signal is discussed.
Keywords: Charge pumping (CP); interface state density; near-interface states; nitrogen passivation; silicon carbide (SiC) MOSFETs